Pengembangan Lembar Kerja Siswa Berbasis Problem Based Learning (PBL) Pada Materi Penerapan Barisan Dan Deret - Feli Ramury; Gustina Gustina; Agustiany Dumeva Putri (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2020)
This study aimed to produce valid and practical student worksheets based on Problem Based Learning at the implementation of row and series at XI grade in MAN Palembang. The research method was used a development research method consisting of the Preliminary stage (the analysis and designing phase) and the prototyping stage using formative evaluation flow (self-evaluation, one to one, small groups, and field tests). Data collection was carried out using walkthrough sheets, questionnaires, interviews, and documentation. The subjects of this study were students of XI grade with a total of the sample was 46 students. From the research results, obtained a valid and practical worksheet by looking at comments/suggestions from the validator and students adjusted for indicator of validity and practicality.